A Study of Two Highly Active, Air‐Stable Iron(III)‐μ‐Oxo Precatalysts: Synthetic Scope of Hydrophosphination using Phenyl‐ and Diphenylphosphine. Issue 15 (25th April 2016) - Gallagher, Kimberley J.; Espinal‐Viguri, Maialen; Mahon, Mary F.; Webster, Ruth L.
Abstract: The importance of phosphines in synthetic chemistry cannot be underestimated. Catalytic hydrophosphination offers an ideal method to prepare P−C bonds without the need for harsh reaction conditions or stoichiometric amounts of waste by‐product. We herein report our studies into two biocompatible iron(III) complexes in hydrophosphination chemistry using diphenylphosphine under mild and benign reaction conditions (room temperature, solvent‐free) and our extended exploration of hydrophosphination with phenylphosphine, which can be tuned to operate in the absence of catalyst under thermal conditions for single hydrophosphination or solvent‐free with an iron(III) precatalyst to generate the products of double hydrophosphination. Abstract :